Etnomatematika pada Gerabah Hias Tradisional Kampiri: Perspektif Geometri, Topologi, dan Pembelajaran dalam Kalkulus Integral - Jafaruddin; Arib, Muhammad Rifai; Wahyuni, Andi Rini Tri; Azzahrah, Luthfiyyah; Azzahra, Nazwa; Chaerani, Annisa; Asy-Syarif, Fathimah Zahra Ar Rosyidah (Issues in Mathematics Education (IMED), 2024)
The decorative pottery of Kampiri from Kampiri Village, Wajo Regency, South Sulawesi, is tangible evidence of Indonesia's rich cultural heritage and local wisdom. This study explores the hidden meanings behind the beauty of Kampiri pottery through a geometric and topological approach. By analyzing the shapes, structures, and ornaments of the pottery, this research aims to understand the application of geometric and topological principles in the design of Kampiri's traditional artwork. Additionally, this study integrates concepts from integral calculus to assess and measure the curvature and complex surface areas of the pottery. This research uses a qualitative descriptive approach with ethnographic methods, involving direct interaction with artisans and field observations. Data collected includes the shapes, structures, ornaments, and pottery-making processes. Integral calculus analysis is applied to explore the relationship between geometric design and numerical values, such as volume and surface area, present in Kampiri pottery. The results of this study are expected to provide new insights into Kampiri pottery, open opportunities for the development of geometric, topological, and integral calculus applications in Nusantara art and design, and enhance appreciation for the local cultural heritage rich in meaning and aesthetic value. This approach to learning integral calculus is also expected to serve as an innovative method for understanding and appreciating traditional Indonesian art through a deeper mathematical perspective.